Detection of Species DNA in Chicken Meatball Products Using NGF Genes as Molecular Markers: Detection of Species DNA in Chicken Meatball Products Using NGF Genes as Molecular Markers - Alfi Sophian (FKIP, Universitas Palangka Raya, 2021)
Species DNA detection in chicken meatball products using the NGF gene as a molecular marker was carried out to see if the NGF gene could be used to test species DNA detection in chicken meatball processed food products. The test method used in this study is the SYBR green test method which is read using real-time PCR and the extraction technique used is the centrifuge column technique. The test results in this technique can be in the form of Ct (Cycling) and Tm (Melting Temperature) values. The results showed that the DNA isolation carried out showed that the concentration and purity of the isolated DNA were in the range of 51,100 ng/µL – 52,300ng/µL with an average of 51,883 ng/µL. As for the value of purity is the absorption value measured at wavelength A260/A280, the results are obtained in the range between 1,850 – 1,920 with an average of 1,880. The results of the real-time PCR analysis obtained the Ct value of the chest sample at 21.10, the Ct LOD value at 25.20 and the positive control Ct value at 20.30. For the Tm value of the busty sample at 78.20, the Tm LOD value at 78.80 and the positive control Tm value at 79.10. Based on the results of this study, it can be concluded that the genetic markers of the NGF gene can be used to test specific DNA detection of chicken species in processed chicken meatball products so that this test method can be used to detect species DNA.